Universal Soldier: The Return - Mic Rodgers; Bargen, Daniel von, 1950-; Heidi Schanz; Justin Lazard; Kiana Tom; Michael Jai White; Xander Berkeley; JeanClaude Van Damme (USA Baumgarten-Prophet Entertainment, 1999)
Luc Devereaux, the only surviving member of the original Universal Soldier Team. He now works with Dylan Cotner, on a project to create and improve a new Universal Soldier. Their plan is for the Universal soldier or UNISOLS to be controlled by a computer they call SETH. When the government decides to terminate the project, which includes shutting down SETH. SETH, not wanting this to happen, takes steps to prevent this. He first kills Dylan. He then has himself transfered into a body. He then seeks out Luc Devereaux, who is the only person who knows the code that will stop his program from being deleted. So he sends out all the UNISOLS to get him. Luc must try and stay away until SETH program is deleted. But SETH has targeted his daughter as possible leverage.
The ""universal soldiers"" (led by Van-Damne) must fight the whole army. When the military's supercomputer S.E.T.H (White) gets out of control
Richard Rothstein
Language(s): English
Subtitle(s): English, Dutch, Czech, Hebrew, Hindi, Icelandic, Polish, Turkish
Keywords: Adventure; SciFi; Action